2012
DOI: 10.1093/ntr/nts246
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Social, and Environmental Factors Associated With Support for Smoke-Free Housing Policies Among Subsidized Multiunit Housing Tenants

Abstract: introduction: Mandatory smoke-free policies in subsidized, multiunit housing (MUH) may decrease secondhand smoke exposure in households with the highest rates of exposure. Ideally, policies should be based on a strong understanding of factors affecting support for smoke-free policies in the target population to maximize effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
3
39
1
Order By: Relevance
“…10 Prevalence of cigarette smoking varied across studies, from 8% 10 to 48%. 17 Half of the studies focused on lowincome residents and/or low-income housing. 10-12 17 22 In four studies, the majority of surveyed MUH residents were racial/ ethnic minorities; 10 11 17 23 in another four studies, greater than 85% were Caucasian.…”
Section: Muh Resident Studies Study Methodologymentioning
confidence: 99%
“…10 Prevalence of cigarette smoking varied across studies, from 8% 10 to 48%. 17 Half of the studies focused on lowincome residents and/or low-income housing. 10-12 17 22 In four studies, the majority of surveyed MUH residents were racial/ ethnic minorities; 10 11 17 23 in another four studies, greater than 85% were Caucasian.…”
Section: Muh Resident Studies Study Methodologymentioning
confidence: 99%
“…23 In addition, residents receiving government subsidies tend to support completely smoke-free building policies. 31 The growing body of evidence supports efforts by HUD to ban smoking completely in all areas of government-subsidized housing. 23 We had several other groups with lower likelihood of reporting incursions.…”
Section: Continuedmentioning
confidence: 99%
“…As seen in Table 1, in the overall population, a higher percentage of those aged 65 and over supported the ban in bars compared to only 48.6% of youth (ages [15][16][17][18][19][20][21][22][23][24]. Nonsmokers showed that older adults (>65 years old), females, those with lower education, widowed, retired and those who believed SHS causes lung cancer had higher percentages of support than their respective modalities (Table 1).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Support for smoking bans identifies the need for behavioral changes at societal 23 and individual levels 24 . Therefore, the aim of the current study was to summarize the characteristics of supporters of the smoking ban in bars by smoking status in Greece and to identify factors related to supporting the ban in bars using the Global Adult Tobacco Survey (GATS) data, so as to help design tools that will improve support and compliance of the smoking ban and consequently improve smoking prevention and cessation throughout Greece and internationally.…”
mentioning
confidence: 99%